Antiinflammatory Activity of the Fruits of Ricinus communis Linn - Bhitre, M.J.; Fulmali, Sushma; Anwikar, Shraddha; Patil, Shrutika (Asian Journal of Chemistry, 2010)
The methanolic, ethanolic, chloroform, ethyl acetate and petroleum ether extracts of fruits of Ricinus communis Linn was tested to study the antiinflammatory activity using the technique of carrageenan induced paw edema in albino rats. The extract showed significant antiinflammatory activity comparable to the reference standard aspirin.